THE MAIN CHARACTER’S DEVELOPMENT IN MANGA HELL’S PARADISE: JIGOKURAKU BY YUJI KAKU: A FREUDIAN PSYCHOANALYSIS - Armando, Michael; Pandin, Moses Glorino Rumambo; Datau, Rizal Octofianto (Jurusan Sastra Indonesia, 2024)
This research aims to analyze the psychological development of the main character